Rhinometric evaluation of nasal cavity geometry and its relation to the upper arch transverse distance - João Batista Paiva; Adriana Silva Alves; Annelise Nazareth Cunha Ribeiro; José Rino Neto; Solange Mongeli de Fantini (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The objective of this study was to evaluate children's respiratory patterns in the mixed dentition, by means of acoustic rhinometry, and its relation to the upper arch width development. Fifty patients were examined, 25 females and 25 males with mean age of eight years and seven months. All of them were submitted to acoustic rhinometry and upper and lower arch impressions to obtain plaster models. The upper arch analysis was accomplished by measuring the interdental transverse distance of the upper teeth, deciduous canines (measurement 1), deciduous first molars (measurement 2), deciduous second molars (measurement 3) and the first molars (measurement 4). The results showed that an increased left nasal cavity area in females means an increased interdental distance of the deciduous first molars and deciduous second molars and an increased interdental distance of the deciduous canines, deciduous first and second molars in males. It was concluded that there is a correlation between the nasal cavity area and the upper arch transverse distance in the anterior and mid maxillary regions for both genders.